Economic Efficiency of Asset Recovery Mechanisms in Corruption Cases: A Law and Economics Approach - Ridwan Arifin; Indah Sri Utari (The Indonesian Journal of Economic Analysis of Law, 2026)
Asset recovery has become a central strategy in combating corruption by targeting the economic benefits obtained through criminal activities. This study analyzes the economic efficiency of asset recovery mechanisms in corruption cases in Indonesia using the framework of Economic Analysis of Law. The research examines whether the confiscation, forfeiture, and recovery of illicit assets provide greater social benefits than reliance on imprisonment as the primary criminal sanction. A normative legal methodology is employed to evaluate relevant legislation, legal principles, and enforcement practices, while economic analysis is used to assess efficiency, deterrence, and welfare outcomes. The findings demonstrate that asset recovery contributes significantly to deterrence by eliminating the financial incentives associated with corruption. Unlike imprisonment, which primarily imposes personal restrictions on offenders, asset recovery directly restores economic resources to the state and reduces the profitability of criminal conduct. However, practical challenges such as asset concealment, cross-border financial transactions, and procedural complexities continue to hinder effective implementation. The study argues that strengthening asset tracing, enhancing inter-agency cooperation, and expanding international legal assistance are essential to maximizing recovery outcomes. Ultimately, the research concludes that asset recovery represents a more economically efficient instrument for addressing corruption because it simultaneously punishes offenders, compensates public losses, and improves social welfare. Integrating economic efficiency into anti-corruption strategies can enhance the effectiveness of criminal law enforcement and support sustainable governance reforms.